2013
DOI: 10.1371/journal.pgen.1003263
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Drosophila Metamorphosis by Xenobiotic Response Regulators

Abstract: Mammalian Nrf2-Keap1 and the homologous Drosophila CncC-dKeap1 protein complexes regulate both transcriptional responses to xenobiotic compounds as well as native cellular and developmental processes. The relationships between the functions of these proteins in xenobiotic responses and in development were unknown. We investigated the genes regulated by CncC and dKeap1 during development and the signal transduction pathways that modulate their functions. CncC and dKeap1 were enriched within the nuclei in many t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
95
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 65 publications
(97 citation statements)
references
References 44 publications
2
95
0
Order By: Relevance
“…Opposite effects of dKeap1 and CncC on transcription of xenobiotic response genes were revealed in our study and also previously reported. 11,12 This is consistent with the conserved function of Keap1/dKeap1 as suppressor of Nrf2/CncC. I hypothesize that Keap1 regulates xenobiotic response genes through inhibiting nuclear Nrf2 levels, while regulates some developmental genes through facilitating Nrf2 binding to chromatin ( Fig.…”
Section: Dkeap1 On Chromatinsupporting
confidence: 75%
See 2 more Smart Citations
“…Opposite effects of dKeap1 and CncC on transcription of xenobiotic response genes were revealed in our study and also previously reported. 11,12 This is consistent with the conserved function of Keap1/dKeap1 as suppressor of Nrf2/CncC. I hypothesize that Keap1 regulates xenobiotic response genes through inhibiting nuclear Nrf2 levels, while regulates some developmental genes through facilitating Nrf2 binding to chromatin ( Fig.…”
Section: Dkeap1 On Chromatinsupporting
confidence: 75%
“…16,17 However, ubiquitinated Nrf2 is prominently nuclear in HepG2 cells. 16 We found that both dKeap1 and CncC predominantly localize to the nuclei of a number of Drosophila tissues, 11 suggesting that dKeap1 interacts with CncC mainly in the nuclei. Therefore, Keap1/dKeap1 may regulate Nrf2/CncC using multiple mechanisms that are not mutually exclusive.…”
Section: Dkeap1 On Chromatinmentioning
confidence: 83%
See 1 more Smart Citation
“…In a Drosophila model of noncardiac muscle laminopathies, Cap‐and‐collar C (CncC) [the orthologue of mammalian nuclear erythroid 2‐related factor 2 (Nrf2)] redox transcriptional regulator (Deng & Kerppola, 2013, 2014) accumulated in myonuclei and activated cellular detoxification genes (Dialynas et al., 2015). To determine whether CncC accumulated in this cardiac model of laminopathies, hearts expressing wild‐type and mutant LamC were stained with antibody to CncC (Deng & Kerppola, 2013, 2014). Hearts expressing wild‐type LamC showed CncC localization within the cytoplasm (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Nuclear CncC (Nrf2) is a characteristic of redox imbalance (Deng & Kerppola, 2013, 2014). To determine the redox status of the hearts, reduced (GSH) and oxidized (GSSH) glutathione were measured (Anderson, 1985; Dialynas et al., 2015).…”
Section: Resultsmentioning
confidence: 99%